Beyond Profitability: Economic Trade-Offs and Socio-Cultural Drivers of The Transition from Tuak to Palm Sugar Production in Rural Indonesia - Mila Quinsy Calista; Eliana Wulandari; Tuti Karyani (Jambura Agribusiness Journal, 2025)
Rural livelihood decisions are not always driven by profit maximization, particularly when economic activities intersect with social, cultural, and religious values. This study examines the transition from Tuak, a traditional fermented palm beverage, to palm sugar production in Lareh Sago Halaban, West Sumatra, Indonesia, by assessing both the economic consequences and the non-economic motivations underlying producers’ decisions. A census survey was conducted involving 18 palm-sap processors who had previously produced Tuak and subsequently shifted to palm sugar production. Producers’ motivations were examined descriptively using Maslow’s hierarchy of needs, while changes in income before and after the transition were evaluated using the Wilcoxon signed-rank test because the paired income data did not satisfy the normality assumption. The results reveal a clear economic–social trade-off. Fifteen of the 18 producers experienced lower income after shifting to palm sugar production, whereas three producers achieved higher income through product diversification into palm sugar powder, liquid palm sugar, and fresh palm sap. The Wilcoxon test confirmed a statistically significant difference in income before and after the transition (Z = −2.156, p = 0.031). Despite the higher economic returns associated with Tuak production, producers continued to shift toward palm sugar because of greater perceived security, social acceptance, personal pride, and opportunities for self-development. These findings demonstrate that livelihood transformation should be understood as a multidimensional decision in which economic returns are weighed against socio-cultural utility. Policies supporting value-added processing, product diversification, producer organizations, and market development are therefore essential to make socially preferred livelihood transitions economically sustainable.